Slaughter on a snowy morn : a tale of murder, corruption and the death penalty case that shocked America - Evans, Colin, 1948- (London : Icon, 2011)
TRUE CRIME. Sing Sing Prison, New York, July 1916. Charles Frederick Stielow, a 37-year-old farmhand with the mind of an infant, is just minutes away from the electric chair for a double murder he didn't commit. With a vengeful legal system baying for blood, his situation looks hopeless. Eight blocks away, Stielow's wife sobs helplessly in her hotel room, certain she will never see her husband alive again...'Slaughter on a Snowy Morn' is the first full account of how Charles Stielow, convicted of murdering a wealthy landowner and his housekeeper, became the central figure in one of the most fascinating yet little-known stories in criminal history.
Includes appendices and notes.
Includes bibliographical references (p. [389]-400).
Keywords: Stielow, Charles -- Trials, litigation, etc; Forensic sciences -- History; Trials (Murder) -- New York (State) -- New York -- History; Judicial error -- New York (State) -- New York -- History